Direct activation of the proposed anti-diabetic receptor, GPR119 in cardiomyoblasts decreases markers of muscle metabolic activity. (15th February 2015) - Cornall, Lauren M.; Hryciw, Deanne H.; Mathai, Michael L.; McAinch, Andrew J.
Highlights: GPR119 agonists are being developed for treating type 2 diabetes. GPR119 protein is expressed in cardiac muscle. GPR119 activation decreased markers of metabolism in cardiac myoblasts. Lipid exposure altered the effects of GPR119 agonism in cardiac myoblasts. GPR119 may have differing effects dependent on overall metabolic health. Abstract: GPR119 agonists are emerging rapidly as a pharmaceutical treatment of diabetes. Diabetes is a known risk factor for cardiovascular disease yet the cardiac-specific consequences of GPR119 activation are unknown. This study demonstrated that GPR119 agonism in cardiac myoblasts reduces metabolic activity in high and low concentrations of fatty acids, with high concentrations of palmitate largely attenuating the effects of the GPR119 agonist, PSN632408. The effects of GPR119 activation on gene and protein markers of metabolism were dependent on fatty acid exposure. Activating GPR119 did not affect cell hypertrophy of lipid accumulation regardless of lipid exposure. These results suggest that the pathways activated in response to GPR119 modulation in cardiac muscle cells differ between healthy and metabolically dysregulated states. However regardless of the pathway activated by GPR119, these effects may cause detrimental reductions to oxidative/metabolic capacity under both conditions. Thus further development of GPR119 agonists for treating metabolic diseases is warranted.